IFAS Standardized Nutrient Recommendations for Vegetable Crop Production in Florida - Rao S. Mylavarapu; George J. Hochmuth; Guodong Liu (EDIS, 2017)
This publication presents the fertilization recommendations for vegetable crops based on soil tests performed by the IFAS Extension Soil Testing Laboratory (ESTL). It contains the basic information from which ESTL soil-test reports and fertilization recommendations are generated. Additional information on nutrient recommendations is presented in the Vegetable Production Handbook of Florida, 2017-2018. Similarly, IFAS Standardized Nutrient Recommendations for Agronomic Crops can be found in SL129 (Mylavarapu, 2015).